Application of cholecystic duct plasty in the prevention of biliary complications following orthotopic liver transplantation - Wang, Jing; Cui, Song-ping; Lyu, Shao-cheng; Chen, Qing; Huang, Jin-can; Wang, Han-xuan; He, Qiang; Lang, Ren (Frontiers in Surgery, 2023)
Background The purpose was aimed to evaluate the safety and effectiveness of cholecystic duct plasty (CDP) and biliary reconstruction techniques preventing biliary complications following orthotopic liver transplantation (OLT) first proposed by our center. Methods 127 enrolled patients who underwent LT in our center from January 2015 to December 2019 were analyzed retrospectively. According to the mode of biliary tract reconstruction, patients were divided into CDP group (Group 1, n = 53) and control group (Group 2, n = 74). The differences of perioperative general data, biliary complications and long-term prognosis between two groups were compared and analyzed. Results All patients completed the operation successfully, the incidence of perioperative complications was 22.8%. There was no significant difference in perioperative general data and complications between the two groups. Follow-up ended in June 2020, with a median follow-up period of 31 months. During the follow-up period, biliary complications occurred in 26 patients, with an overall incidence of 20.5%. The overall incidence of biliary complications and anastomotic stenosis in Group 1 was lower than that in Group 2 (P < 0.05). There was no significant difference in overall prognosis between the two groups (P = 0.274), however, the cumulative incidence of biliary complications in Group 1 was lower than that in Group 2 (P = 0.035). Conclusion Reconstruction of common bile duct by CDP represents considerable safety and practicability, particularly for patients with small diameter of common bile duct or wide discrepancy of bile duct size between donor and recipient.